Synaptic plasticity in animal models of stress : serotonergic mechanisms - Ryan, Benedict K. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2005)
The inhibitory effect of acute elevated platform stress exposure on synaptic plasticity in the CA1 region of the hippocampus in vivo was investigated. Such stress exposure was confirmed to inhibit subsequent long term potentiation (LTP) induction in urethane anaesthetised rats. We investigated the effect of modulation of the serotonergic system on this stress-induced inhibition of LTP induction. 5-hydroxytryptamine (5-HT) levels are reported to be raised following acute stress exposure and is thought to contribute to stress-induced inhibition of LTP in CA1. We found that injection of the 5-HT releasing agent (±)fenfluramine ((±)-N-Ethyl-α-methyl-m-[trifluoromethyl]phenethylamine) post-stress exposure enabled the induction of LTP. We also investigated distinct 5-HT receptors with respect to their participation in the (±)fenfluramine mediated abrogation of the inhibitory effect of stress on the induction of LTP. We identified 5-HT2 receptor activation as being of importance in mediating the enablement of the induction of LTP in (±)fentluramine treated animals which had been previously exposed to acute elevated platform stress. We also investigated agonists of 5-HT2 receptors and found that activators of 5-HT2b/2c (mCPP: 1-(3-Chlorophenyl)piperazine hydrochloride), 5-HT2b (BW723c86: α-Methyl-5-(2-thienylmethoxy)- 1H-indole-3-ethanamine hydrochloride) or 5HT2C (MK-212: 6-Chloro-2-( 1-piperazinyl) pyrazine hydrochloride) receptors enabled the induction of LTP in animals exposed previously to acute elevated platform stress.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin